Can we evaluate population screening strategies in UK general practice? A pilot randomised controlled trial comparing postal and opportunistic screening for genital chlamydial infection. Issue 3 (11th February 2005) - Senok, Abiola; Wilson, Phil; Reid, Margaret; Scoular, Anne; Craig, Neil; McConnachie, Alex; Fitzpatrick, Bridie; MacDonald, Alison
Abstract : Study objective: To assess whether opportunistic and postal screening strategies for Chlamydia trachomatis can be compared with usual care in a randomised trial in general practice. Design: Feasibility study for a randomised controlled trial. Setting: Three West of Scotland general medical practices: one rural, one urban/deprived, and one urban/affluent. Participants: 600 women aged 16–30 years, 200 from each of three participating practices selected at random from a sample of West of Scotland practices that had expressed interest in the study. The women could opt out of the study. Those who did not were randomly assigned to one of three groups: postal screening, opportunistic screening, or usual care. Results: 38% (85 of 221) of the approached practices expressed interest in the study. Data were collected successfully from the three participating practices. There were considerable workload implications for staff. Altogether 124 of the 600 women opted out of the study. During the four month study period, 55% (81 of 146) of the control group attended their practice but none was offered screening . Some 59% (80 of 136) women in the opportunistic group attended their practice of whom 55% (44 of 80) were offered screening. Of those, 64% (28 of 44) accepted, representing 21% of the opportunistic group. Forty eight per cent (59 of 124) of the postal group returned samples. Conclusion: A randomised controlled trial comparing postal and opportunistic screening for chlamydial infection in general practice is feasible, although resource intensive. There may be problems with generalising from screening trials in which patients may opt out from the offer of screening.